2022
DOI: 10.1002/fft2.139
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose administration of purified cyanidin‐3‐glucose or a blackberry extract causes improved mitochondrial function but reduced content in 3T3‐L1 adipocytes

Abstract: Berry consumption shows antiobesity and antidiabetic effects in animals and humans.Anthocyanin or berry extracts increase insulin sensitivity, reduce lipid droplet formation, and cause a white-to-brite phenotypic switch of adipocytes in vitro. The objective of this study was to investigate effects of cyanidin-3-glucoside (C3G) or blackberry extract (BBE) on cellular respiration of a fatty acid substrate in differentiated adipocytes. In separate experiments, 3T3-L1 adipocytes were treated with 0, 150 nM, or 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…C-3-ARA has also been detected in other wild berries ( Mieres-Castro et al, 2019 ; Sánchez-Gavilán et al, 2021 ), and has been suggested to possess beneficial health properties through mitochondrial regulation ( Jung et al, 2022 ). C-3-GLU and C-3-GAL are common anthocyanins in berries and other foods ( Bellocco et al, 2016 ; Liang et al, 2021 ; Solverson et al, 2022 ) and their health benefits have been studied more extensively ( Chen et al, 2022 ; Gan et al, 2020 ; Liang et al, 2021 ; Tan et al, 2019 ). Therefore, with two to ten-fold the amount of cyanidin derivatives compared to blueberries, huckleberries can be considered as excellent sources of dietary cyanidins with health protective effects.…”
Section: Resultsmentioning
confidence: 99%
“…C-3-ARA has also been detected in other wild berries ( Mieres-Castro et al, 2019 ; Sánchez-Gavilán et al, 2021 ), and has been suggested to possess beneficial health properties through mitochondrial regulation ( Jung et al, 2022 ). C-3-GLU and C-3-GAL are common anthocyanins in berries and other foods ( Bellocco et al, 2016 ; Liang et al, 2021 ; Solverson et al, 2022 ) and their health benefits have been studied more extensively ( Chen et al, 2022 ; Gan et al, 2020 ; Liang et al, 2021 ; Tan et al, 2019 ). Therefore, with two to ten-fold the amount of cyanidin derivatives compared to blueberries, huckleberries can be considered as excellent sources of dietary cyanidins with health protective effects.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, 3T3-L1 adipocytes increased maximal respiration when incubated with malvidin 3-glucoside [ 5 ]. In addition, our group recently found a greater oxidative capacity of 3T3-L1 adipocytes treated with cyanidin 3-glucoside or blackberry extract [ 32 ]. Oxygen consumption was higher in all respiration states.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, pinostrobin is used as a quality indicator of pigeon pea leaves for its high content and characteristic existence (Wang & Li, 2022). High level of bioactive phytochemicals often suggests high potential in the prevention/treatment of pathological conditions and diseases, including anti‐osteoporosis (Lai Lijin, 2020; Linan, 2014; Liu et al., 2022), anti‐inflammatory (Huang et al., 2016; Lai et al., 2012), anti‐cancer (Abo‐Zeid et al., 2018; Luo et al., 2010), anti‐bacterial (Kong et al., 2010), anti‐obesity (Solverson et al., 2022), and anti‐viral (Nwodo et al., 2011; Zu et al., 2010). On this basis, we discover a research gap that no data are reported for pigeon pea about the changing trend of any single polyphenols during sprouting, microgreens, and mature leaves.…”
Section: Biological Strategies As a Promising Approach To Promote The...mentioning
confidence: 99%